B lymphocytes in neuromyelitis optica. Issue 3 (June 2015) - Bennett, Jeffrey L.; O'Connor, Kevin C.; Bar-Or, Amit; Zamvil, Scott S.; Hemmer, Bernhard; Tedder, Thomas F.; von Büdingen, H.-Christian; Stuve, Olaf; Yeaman, Michael R.; Smith, Terry J.; Stadelmann, Christine
Abstract : Neuromyelitis optica (NMO) is an inflammatory autoimmune disorder of the CNS that predominantly affects the spinal cord and optic nerves. A majority (approximately 75%) of patients with NMO are seropositive for autoantibodies against the astrocyte water channel aquaporin-4 (AQP4). These autoantibodies are predominantly IgG1, and considerable evidence supports their pathogenicity, presumably by binding to AQP4 on CNS astrocytes, resulting in astrocyte injury and inflammation. Convergent clinical and laboratory-based investigations have indicated that B cells play a fundamental role in NMO immunopathology. Multiple mechanisms have been hypothesized: AQP4 autoantibody production, enhanced proinflammatory B cell and plasmablast activity, aberrant B cell tolerance checkpoints, diminished B cell regulatory function, and loss of B cell anergy. Accordingly, many current off-label therapies for NMO deplete B cells or modulate their activity. Understanding the role and mechanisms whereby B cells contribute to initiation, maintenance, and propagation of disease activity is important to advancing our understanding of NMO pathogenesis and developing effective disease-specific therapies.